(untitled) (Eurasian Research Bulletin, 2024)
The article analyzes the methods of evaluating the efficiency of the use of economic resources in industrial enterprises in the context of the development of modern industries. In the process of comprehensive assessment of the efficiency of industrial enterprises, classification of its criteria and indicators is scientifically based. Also, the method of evaluating the efficiency of the use of economic resources in the enterprise has been improved based on the factors determining the impact on the rational use of resources and the indices describing the economic development of their enterprises and industrial areas.